2017
DOI: 10.1558/cj.26754
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Audiovisual Media on L2 Listening Comprehension: A Preliminary Study in French

Abstract: The purpose of the present study was to determine whether integrating online audiovisual materials into the listening instruction of L2 French learners would have a measurable impact on their listening comprehension development. Students from two intact sections of second-semester French were tested on their listening comprehension before and after a four-week learning phase during which the treatment group received listening instruction via audiovisual materials while the control group completed a different l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…The didactic use of cinema helps high school French learners to enhance their listening skills because, when watching films, students understand the aural input they receive more easily thanks to the visual support (Becker and Sturm;. Moreover, the cinema-based approach also helps high school French learners to hone their reading skills on the grounds that it encourages them to read more.…”
Section: The Linguistic Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…The didactic use of cinema helps high school French learners to enhance their listening skills because, when watching films, students understand the aural input they receive more easily thanks to the visual support (Becker and Sturm;. Moreover, the cinema-based approach also helps high school French learners to hone their reading skills on the grounds that it encourages them to read more.…”
Section: The Linguistic Dimensionmentioning
confidence: 99%
“…Moreover, the only empirical studies which have been conducted so far have not shed enough light on this matter because they have mostly examined the University context, teacher perceptions, and only a very limited number of the advantages of this methodology has been tested (Arey, 1993;Karadag, 2009;Kerrita, 2017;Pegrum et al, 2005;Rouxel-Cubberly, 2014). In fact, the results of the bibliographic search reveal that the most recent studies on this topic have revolved around just one benefit of the cinema-based approach, mainly, around vocabulary acquisition (Bairstow & Lavaur, 2017;Kanellopoulou 2019), listening comprehension (Becker & Sturm, 2017), and cultural awareness (Mencová, 2016;Molina-García & Rúa, 2017). Thus, producing empirical research which examines high school students' perception and testing all the advantages this method has for them are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan hasil angket penjajakan analisis kebutuhan sebanyak 88% menjawab perlunya pengembangan media sebagai penunjang pembelajaran di SD. Media audio ini digunakan sarana untuk meningkatkan pemahaman siswa dalam memadukan kemampuan visual dan audio dalam memahami materi tematik di SD (Becker, 2013). Media audio tematik diadaptasi dari teks tema yang terdapat dalam buku siswa.…”
Section: Analisis Kebutuhanunclassified
“…The use of authentic tools of all types in foreign language classes has been well-documented. A number of comprehensive reviews of this topic have been published in the past two decades that provide both evidence of its application, and the theoretical underpinnings, in a variety of cultures (see Al-Azri and Al-Rashdi, 2014; Becker and Strum, 2017; Emerick, 2019; Gruba, 2006; Mayer, 1997; McNutty and Lazarevic, 2014; Oritz et al, 2012; Pinner, 2016; Vanderplank, 2010). Research has shown authenticity has a positive impact on classroom outcomes, such as learning tasks (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, more experimentally controlled empirical studies examining the benefits of authentic audio-visual material have been published (e.g. Ahour and Rahbar, 2014; Bajrami and Ismaili, 2016; Becker and Strum, 2017; Rahbar, 2014; Sabet and Mahsefet, 2012). In general, these empirically based studies compare samples of classes using authentic instructional material over a period of class time, ranging from several weeks to a full term, with a control group not using the materials.…”
Section: Literature Reviewmentioning
confidence: 99%